Factors that influence the choice and consumption of raw foods - SAMPAIO, Andressa Aparecida Jacinto; PEREIRA, Marcelo Martins; COSTA, Tatiane Barboza da (130, 2020)
Eating is a basic activity to obtain energy and nutrition necessary for life. When chewing, food is broken by the teeth and dissolved by saliva. Foodborne illnesses have increased in recent years, greater impact on the health and economy of developing countries than in developing countries developed countries. During chewing, you will taste, taste and texture and will help to add a feeling of food. Uncooked foods are an integral component of human nutrition and are a necessary precondition for an intact immune system. Databases such as MEDLINE/Pubmed, Scielo and Google Scholar were consulted. The objective of this work is to expose the advantages and the necessary precautions for the consumption of raw foods by humans. The dangers of consuming raw foods are recognized, since food poisoning is the greatest risk factor for health. Therefore, the present study reveals the factors and safety for the consumption of a raw food. RESUMO: Comer é uma atividade básica para obter energia e nutrição necessária para a vida. Ao mastigar, o alimento é quebrado pelos dentes e dissolvido pela saliva. As doenças transmitidas por alimentos aumentaram nos últimos anos, com maior impacto na saúde e na economia dos países em desenvolvimento do que nos países em desenvolvimento dos países desenvolvidos. Durante a mastigação, você sentirá o sabor, o sabor e a textura e ajudará a adicionar uma sensação de comida. Alimentos não cozidos são um componente integral da nutrição humana e são uma pré-condição necessária para um sistema imunológico intacto. Bases de dados como MEDLINE/Pubmed, Scielo e Google Acadêmico foram consultadas. O objetivo deste trabalho é expor as vantagens e os cuidados necessários para o consumo de alimentos crus por humanos. Os perigos do consumo de alimentos crus são reconhecidos, pois a intoxicação alimentar é o maior fator de risco para a saúde. Portanto, o presente estudo revela os fatores e a segurança para o consumo de um alimento cru.
Fatores que influenciam na escolha e no consumo de alimentos crus
Artigo científico válido como TCC.
Keywords: Alimentos naturais; Saúde; Produção Alimentícia